Electron transfer mediated decay of alkali dimers attached to He nanodroplets - Ltaief, L. Ben; Shcherbinin, M.; Mandal, S.; Krishnan, S. R.; Richter, R.; Pfeifer, Thomas; Bauer, Marco; Ghosh, Aryya; Mudrich, M.; Gokhberg, Kirill; LaForge, A. C. (Physical chemistry, chemical physics, 2020)
Alkali metal dimers attached to the surface of helium nanodroplets are found to be efficiently doubly ionized by electron transfer mediated decay (ETMD) when photoionizing the helium droplets. This process is evidenced by detecting in coincidence two energetic ions created by Coulomb explosion and one low-kinetic energy electron. The kinetic energy spectra of ions and electrons are reproduced by simple model calculations based on diatomic potential energy curves, and are in agreement with ab initio calculations for the He-Na2 and He-KRb systems. This work demonstrates that ETMD is an important decay channel in heterogeneous nanosystems exposed to ionizing radiation.
Gesehen am 30.03.2021